Sodium from salts : uses, functions and research needs. (British food journal (Croydon, England), 2002)
Researchers have assessed the effects of different diets on blood pressure. Recent findings indicate that a low fat diet, rich in fruit and vegetables, cansignificantly lower blood pressure, particularly in those with establishedhypertension but also in those with high normal blood pressure who may be atrisk of developing hypertension (Appel et al.